2013
DOI: 10.1056/nejmoa1215740
|View full text |Cite|
|
Sign up to set email alerts
|

Glucose Levels and Risk of Dementia

Abstract: BACKGROUND Diabetes is a risk factor for dementia. It is unknown whether higher glucose levels increase the risk of dementia in people without diabetes. METHODS We used 35,264 clinical measurements of glucose levels and 10,208 measurements of glycated hemoglobin levels from 2067 participants without dementia to examine the relationship between glucose levels and the risk of dementia. Participants were from the Adult Changes in Thought study and included 839 men and 1228 women whose mean age at baseline was 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
459
3
15

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 735 publications
(513 citation statements)
references
References 27 publications
24
459
3
15
Order By: Relevance
“…Diabetes is usually accompanied with a moderate injury in learning and memory. A study published in New England Journal of Medicine in 2013 reported that elevated blood glucose levels would increase the risk of cognitive impairment whether they are suffering from diabetes (Crane et al, 2013). The learning and memory ability will be improved in people suffering from diabetes as the effective control of blood glucose (Vanhanen et al, 1999).…”
Section: Some Common Diseases and Admentioning
confidence: 99%
“…Diabetes is usually accompanied with a moderate injury in learning and memory. A study published in New England Journal of Medicine in 2013 reported that elevated blood glucose levels would increase the risk of cognitive impairment whether they are suffering from diabetes (Crane et al, 2013). The learning and memory ability will be improved in people suffering from diabetes as the effective control of blood glucose (Vanhanen et al, 1999).…”
Section: Some Common Diseases and Admentioning
confidence: 99%
“…Subsequent clinical and epidemiological studies have confirmed this association (reviewed in [4]. In fact, Type 2 diabetes patients can be more than twice as likely to develop AD [2,5]. Collectively, these studies establish that Type 2 diabetes mellitus increases the risk of developing AD.…”
mentioning
confidence: 82%
“…There is growing evidence of an association between type 2 diabetes in older patients and the risk of dementia (vascular and Alzheimer type). 5 A longer duration of diabetes is associated with poorer cognitive performance. 5 The exact mechanism underlying the association between these two entities is a matter of debate, but vascular lesions and repeated hypoglycemia may be contributing factors.…”
Section: How Does the Patient's Frailty Affect Targets For Glycemic Cmentioning
confidence: 99%
“…5 A longer duration of diabetes is associated with poorer cognitive performance. 5 The exact mechanism underlying the association between these two entities is a matter of debate, but vascular lesions and repeated hypoglycemia may be contributing factors. Genetic factors, such as the presence of APOE4, may also be involved.…”
Section: How Does the Patient's Frailty Affect Targets For Glycemic Cmentioning
confidence: 99%
See 1 more Smart Citation